Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls